PP.30.04: ASSOCIATION BETWEEN THE QUALITY OF LIFE AND BLOOD GLUCOSE SCREENING OF CONDUCT AND TRIGLYCERIDES IN PEOPLE WITH HYPERTENSION. (June 2015) - Bachur, C.; Veiga, E.V.; Fava, S.M.C.L.; Machado, J.P.; Silva, P.C.S.
Abstract : Objective: To associate the quality of life and the realization of Blood glucose and triglycerides in people with hypertension assisted by health strategy of the family of a municipality in southern Minas Gerais, Brazil. Design and method: A descriptive cross-sectional and quantitative approach, performed with 397 people with hypertension enrolled in HIPERDIA system. The research project was approved by the Research Ethics Committee of the Ribeirão Preto School of Nursing, University of São Paulo. To collect data, we used instruments for the assessment of blood glucose and triglycerides tests already carried out and the specific instrument Minichal to assess the quality of life. Results: It was found a predominance of females, aged between 50–69 years. Regarding the test results of blood glucose and triglycerides respectively, 98.5% (391) and 98.2% (390) have undertaken these tests. As for the association between the examinations of blood glucose and triglycerides and the quality of life in the multivariate analysis showed a statistically significant association only in conducting examination of triglycerides and the domain mental state of Minichal scale. Conclusions: People with hypertension who took triglycerides have better quality of life that people who have not done in the field of mental state Minichal scale.